2023
DOI: 10.1097/prs.0000000000010573
|View full text |Cite
|
Sign up to set email alerts
|

Towards a consensus approach for assessing capsular contracture severity and progression: A systematic review

Abstract: Capsular contracture (CC) is the most common complication of breast augmentation and reconstruction with implants. [1][2][3][4] The original classification scheme, developed by Spear and Baker, 5 is the most broadly adopted and provides a straightforward metric for evaluating CC in countless studies that have shaped our understanding of outcomes in breast implant surgery. The Baker classification (Table 1) considers physician and patient perceptions of implant palpability, visibility, breast firmness, and pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Capsular contracture, based on our study and according to the data of many authors [3,35], was the main risk for revision operations after aesthetic breast augmentation with breast implants. For example, Henriksen T. F. and coauthors [21] in 2005 found about 22% of capsular contracture as a complication after aesthetic breast plastic surgery.…”
Section: Discussionsupporting
confidence: 53%
“…Capsular contracture, based on our study and according to the data of many authors [3,35], was the main risk for revision operations after aesthetic breast augmentation with breast implants. For example, Henriksen T. F. and coauthors [21] in 2005 found about 22% of capsular contracture as a complication after aesthetic breast plastic surgery.…”
Section: Discussionsupporting
confidence: 53%
“…It has been widely documented in capsules formed around silicone implants and it is indicative of a benign capsule ( 44 ). In fact, its presence is associated with Baker grade I and II capsules while its absence is typical of Baker grades III and IV capsules, possibly linking this formation with a protective effect against capsular contracture ( 43 , 45 , 46 ). Synovial metaplasia was observed to form also with other ADMs.…”
Section: Discussionmentioning
confidence: 99%
“…2B). 38 Histologically, there is fibrous tissue with thick and dense bands of collagen, fibroblasts, macrophages, and lymphocytes (Fig. 2C, D).…”
Section: Pathologic Featuresmentioning
confidence: 98%
“…The US features that suggest capsular contracture include an increased number of radial folds and thickening of the fibrous capsule. 37,38 Breast MRI shows irregular thickening of the capsule, an increased number of folds, and a spherical appearance of the implant (Fig. 2A).…”
Section: Imagingmentioning
confidence: 99%